Bank regulation, risk management, and compliance : theory, practice, and key problem areas - Alexander Dill (2024)
The book establishes a conceptual framework that helps readers to understand bank regulators' expectations for the risk management and compliance functions. Informed by the author's experience at a major credit rating agency in helping to design and implement a ratings compliance system, it explains how the banking business model, through credit extension and credit intermediation, creates the principal risks that regulation is designed to mitigate: credit, interest rate, market, and operational risk, and, more broadly, systemic risk.